DISTANCE LEARNING AS THE NEW REALITY IN TERTIARY EDUCATION: A CASE STUDY - Ілона Густі; Юрій Чотарі; Ілона Лехнер (Novìtnâ Osvìta, 2022)
The year 2020 was a horrible shock for both educators and students worldwide because of the COVID-19 disease. The whole educational process had to undergo cardinal changes in that it was forced to transition from face-to-face to online mode. Distance learning (DL) became the new reality in no time. This unusual situation prompted us to conduct research on what challenges it meant for tutors to cope with the new requirements. The main goal of our case study was to get insights into the altered daily routines of tutors and understand how the system functioned. Another objective of our survey was to provide a brief synthesis of distance learning, based on the academic literature. We have applied the qualitative research design, using a semi-structured interview as a research instrument for collecting data from the respondents. The research sample consisted of thirty-four college tutors teaching language and literature (English, German, Ukrainian, and Hungarian). The participants were requested to reply to eleven questions either online or face-to-face. The results proved how unexpected and difficult it was to move from the classroom to distance education. They emphasized how crucial digital literacy is for both instructors and students. One of the essential implications is that teachers must develop their digital skills in every possible way. The next stage of our research will be to investigate what impact DL has on teachers' and students' physical and psychological well-being.